2013
DOI: 10.1016/j.repbio.2013.01.181
|View full text |Cite
|
Sign up to set email alerts
|

The effects of artificial activation timing on the development of SCNT-derived embryos and newborn piglets

Abstract: This study investigated the effects of two different activation regimens on the developmental potential of somatic cell nuclear transfer (SCNT) embryos and postnatal survivability of the cloned piglets. In vitro matured oocytes were enucleated and reconstructed with porcine fetal fibroblasts. On the basis of the activation regimen used, the reconstructed porcine embryos were allocated into two groups: Group 1-simultaneous electrical pulses and activation group (SFA group); and Group 2-electrical fusion without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In vitro cultured fibroblast cells, which had been derived from the dermointegumentary tissue of fetuses and adult specimens, are the commonly used source of nuclear donor cells in the pig cloning procedure [ 14 18 ]. The degree of molecular and epigenetic differentiation of these cells that is related both to the advanced methylation profile of DNA cytosine residues and to the lysine deacetylation profile of histones forming nucleosomal core of nuclear chromatin often seems to make the converting of the abovementioned covalent modifications back to a totipotent state of embryonic (zygotic) cells impossible.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro cultured fibroblast cells, which had been derived from the dermointegumentary tissue of fetuses and adult specimens, are the commonly used source of nuclear donor cells in the pig cloning procedure [ 14 18 ]. The degree of molecular and epigenetic differentiation of these cells that is related both to the advanced methylation profile of DNA cytosine residues and to the lysine deacetylation profile of histones forming nucleosomal core of nuclear chromatin often seems to make the converting of the abovementioned covalent modifications back to a totipotent state of embryonic (zygotic) cells impossible.…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous nucleoplasmic and cytoplasmic factors derived from the nuclear donor cell, which are responsible for modulating the epigenetic status of genomic DNA, are incorporated together with oocyte mRNA transcripts and proteins, into the remodeled nucleus of the somatic cell (the so-called pseudo-pronucleus). The pseudo-pronucleus is formed following artificial activation of the embryonic developmental program of the reconstructed oocyte [1,[128][129][130][131][132][133][134][135][136][137]. In turn, an overabundance of the somatic cell-derived agents modulating the epigenetic profile of the donor nucleus may remarkably reduce the concentration and activity of the oocyte's epigenetic factors.…”
Section: Direct Intraooplasmic Microinjection Of Karyoplastsmentioning
confidence: 99%
“…For activation, several effective protocols for artificial oocyte activation have been developed. However, most protocols require prolonged exposure to non-specific inhibitors with high variability in results (Bang et al, 2013;Liu et al, 2015;Li et al, 2017). Hence, it has been shown that the use of agents that mimic the physiological activation events, such as the zinc chelator TPEN, through the manipulation of Ca 2þ and Zn 2þ , improved chemical activation and developmental rates of porcine oocytes (Lee et al, 2015;Macedo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%